GEREJA SETAN DAN PROPAGANDANYA DALAM DUNIA HIBURAN - Rijani, Faidillah (Faculty of Ushuluddin and Humanities, 2013)
The movement of Satanism or the so-called Church of Satan appears in America, but it is generally unknown in the Muslim world, especially Indonesia. This article tries to understand the Church of Satan, its ritual and propaganda. This church was established by Anton Szandor Lavey. It is a kind of occultist movement . The ritual of the Church of Satan is based on its âscriptureâ called The Satanic Bible. In the ritual, names of satan are recited and adorned, and sexual intercourses among the participants are common. The Church of Satan uses film, music, and electronic games to propagate itself.